High Density Mapping of Quantitative Trait Loci Conferring Gluten Strength in Canadian Durum Wheat - Ruan, Yuefeng; Yu, Bianyun; Knox, Ron E.; Singh, Asheesh K.; DePauw, Ron; Cuthbert, Richard; Zhang, Wentao; Piche, Isabelle; Gao, Peng; Sharpe, Andrew; Fobert, Pierre (Frontiers in Plant Science, 2020)
Gluten strength is one of the factors that determines the end product quality of durum wheat and is an important breeding target for this crop. To characterize the quantitative trait loci (QTL) controlling gluten strength in Canadian durum wheat cultivars, a population of 162 doubled haploid (DH) lines segregating for gluten strength and derived from cv. Strongfield × cv. Pelissier was used in this study. The DH lines, parents and checks were grown in three years and two seeding dates in each year and gluten strength of grain samples was measured by SDS-sedimentation volume (SV). With a genetic map created by genotyping the DH lines using the Illumina Infinium iSelect Wheat 90K SNP (single nucleotide polymorphism) chip, QTL contributing to gluten strength were detected on chromosome 1A, 1B, 2B and 3A. Two major and stable QTL detected on chromosome 1B (QGlu.spa-1B.1) and 1A (QGlu.spa-1A) explaining 25.4- 40.1% and 13.7-18.7% of the gluten strength variability respectively were consistently detected over three years, with the trait increasing alleles derived from Strongfield. Putative candidate genes underlying the QTL were identified. Two minor QTL (QGlu.spa-3A.1 and QGlu.spa-3A.2) with the trait increasing allele derived from Pelissier were mapped on chromosome 3A explaining up to 8.9% of the phenotypic variance; another three minor QTL (QGlu.spa-2B.1, QGlu.spa-2B.2 and QGlu.spa-2B.3) located on chromosome 2B explained up to 8.7% of the phenotypic variance with the trait increasing allele derived from Pelissier. Multi-environment analysis revealed genetic (QTL) × environment interaction due to the difference of effect in magnitude rather than the direction of the QTL. Eleven pairs of digenic epistatic QTL were identified, with an epistatic effect between the two major QTL of QGlu.spa-1A and QGlu.spa-1B.1detected in 4 out 6 environments. SNPs flanking the QTL interval can be converted to Kompetitive Allele Specific PCR (KASP) markers to be deployed in marker-assisted breeding to increase the efficiency and accuracy of phenotypic selection for gluten strength in durum wheat. The QTL that were expressed consistently across environments are of great importance to maintain the gluten strength of Canadian durum wheat to current market standards during genetic improvement for other traits.